Acoustic channel frequency response estimation using sources of opportunity - Santos, Ana Bela (2017)
This work addresses the usage of ship radiated noise to estimate the ocean acoustic water propagation channel response between two vertical line arrays. We derive an expression for the frequency response channel estimate using a normal mode development based on cross-correlation methods, in a similar way as Roux et al. [1]. Its applicability and limitations in simulated and real conditions is discussed. Simulations are conducted using the normal mode model KRAKEN, based on the experimental setup and environmental parameters gathered during the RADAR' 07 sea trial, off the west coast of Portugal, in July of 2007. In this sea trial two drifting vertical line arrays with 16 and 8 hydrophones were deployed in a range independent bathymetric area, at 300 m and 1.3 km distance from the Research Vessel NRP D. Carlos I, whose track then moved away from the arrays, radiating noise in the frequency band bellow 750 Hz. The wave fronts structure, obtained from actual acoustic data of the above referred sea trial, reveals agreement with the simulations obtained with the proposed approach. These results suggest the feasibility of the method for future application in a passive ocean acoustics tomography framework to the estimation of sound speed perturbations in the water column.